Squamous Cell Carcinoma of perineal area developed from the Buschke–Löwenstein tumor - Stępień, Grzegorz J.; Włodarczyk, Jakub; Włodarczyk, Marcin; Dziki, Łukasz (Folia Medica Cracoviensia, 2023)
The Buschke–Löwenstein tumor is a rare disease associated with human papillomavirus infec-tion. The condition manifests with an ulcerative, exophytic tumor localized in the perineal area. Generally considered as non-cancerous, the growth may develop malignant transformation. Our manuscript high-lights the importance of early diagnosis with histopathological analysis.
Keywords: human papillomavirus; giant condyloma acuminatum; malignant transformation; HPV vaccination; Buschke–Löwenstein tumor